A new species of Lysipomia (Campanulaceae) from Ecuador - Ayers, Tina J.; Sklenář, Petr; Fernández, Diana M. (Phytotaxa, 2017)
Lysipomia petrosa from Azuay province, Ecuador, is described as new and compared with the related species L. bilineata and L. caespitosa.